2021
DOI: 10.3390/w13162287
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Pollution in the Surface Waters from Plain and Mountainous Lakes in Siberia, Russia

Abstract: Microplastics (MPs) contaminations of freshwater and marine environments has become a global issue. Lakes in southern Siberia provide a wide range of ecosystem services and are essential elements in the annual and interannual runoff distribution of the Great Siberian Rivers. However, the extent of their MPs pollution remains unknown. In this paper, for the first time, we analyze the concentrations, composition, and spatial distribution of MPs in six lakes in southern Siberia. The studied lakes are located both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…A similar range (5.4-1292 items/m 2 ) was found in Qinghai Lake (Tibetan Plateau, China) by Xiong et al [57] . Greater abundance (mean value: 2644 items/kg) was reported by Liang et al [64] , who also measured MP occurrence in 12 lakes of the Tibetan Plateau.…”
Section: Microplastics Occurrence In High-mountain Lakesmentioning
confidence: 54%
See 2 more Smart Citations
“…A similar range (5.4-1292 items/m 2 ) was found in Qinghai Lake (Tibetan Plateau, China) by Xiong et al [57] . Greater abundance (mean value: 2644 items/kg) was reported by Liang et al [64] , who also measured MP occurrence in 12 lakes of the Tibetan Plateau.…”
Section: Microplastics Occurrence In High-mountain Lakesmentioning
confidence: 54%
“…Neelavannan et al [62] reported that the most frequent MP size in the sediment samples from Anchar Lake (Himalaya) ranged between 300 and 1000 μm. Smaller particles (ranging 50-500 μm) were reported in sediment samples by Liang et al [64] in 12 remote lakes of the Tibetan Plateau. The same results were shared by Xiong et al [57] who reported MPs ranging in size between 100 and 500 μm in both water and sediment samples from the high-altitude Qinghai Lake (China) and by Negrete Velasco et al [61] for Sassolo Lake (Switzerland), who recorded particles ranging in size between 125 and 500 μm.…”
Section: Microplastics Occurrence In High-mountain Lakesmentioning
confidence: 80%
See 1 more Smart Citation
“…This Special Issue includes studies from different parts of the world, i.e., Russia [2], India [3], and Mediterranean Regions such as Italy [4], Greece [5], and Cyprus [6]. These are mainly baseline studies that monitor microplastics in different areas.…”
mentioning
confidence: 99%
“…There seems to be a trend of correlating the concentration of microplastics with surrounding land uses. Nevertheless, it seems that microplastics are present in all areas even in remote rural ones [2,3], as well as in agricultural lands [5]. However, the presence of a wastewater treatment plant (WWTP) in the vicinity seems to play a crucial role in the concentration of microplastics in a lake [4].…”
mentioning
confidence: 99%